Evaluation of the routine use of the anaerobic bottle when using the BACTEC blood culture system - Karunakaran, R.; Raja, N.S.; Quek, K.F.; Hoe, V.C.W.; Navaratnam, P. (Elsevier, 2007)
The established practice of sending blood cultures in an aerobic-anaerobic pair of bottles has been questioned in recent years, and this study was conducted to evaluate the routine use of an anaerobic bottle in the BACTEC blood culture set at the University of Malaya Medical Centre, Kuala Lumpur, from January to December 2004. A total of 11,663 paired blood culture sets were received, of which 3326 were from pediatric patients and 8337 were from adult patients. The overall positive isolation rate was 15%; the positive isolation rate on excluding the anaerobic bottles was 13%. Overall, there were significantly more organisms isolated from the aerobic bottle (p<0.05); however, the best yield was obtained on using the paired aerobic-anaerobic bottles. Among the positive blood culture sets, organisms were isolated from the anaerobic bottle alone in 15.2% of the pediatric sets and in 18.1% of the adult sets. Organisms that grew more frequently in the anaerobic bottle were anaerobes and some facultative anaerobes; however, the difference was not statistically significant except for anaerobes in the adult sets. We recommend that when culturing blood, an aerobic-anaerobic pair of bottles be used rather than an aerobic-aerobic pair, to optimize the recovery of a wider spectrum of organisms, including obligatory anaerobes.